2021
DOI: 10.1101/2021.04.02.438217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HAP40 orchestrates huntingtin structure for differential interaction with polyglutamine expanded exon 1

Abstract: Huntington's disease results from expansion of a glutamine-coding CAG tract in the huntingtin (HTT) gene, producing an aberrantly functioning form of HTT. Both wildtype and disease-state HTT form a hetero-dimer with HAP40 of unknown functional relevance. We demonstrate in vivo that HTT and HAP40 cellular abundance are coupled. Integrating data from a 2.6 Å cryo-electron microscopy structure, cross-linking mass spectrometry, small-angle X-ray scattering, and modeling, we provide a near-atomic-level view of HTT,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
(84 reference statements)
2
0
1
Order By: Relevance
“…The quality of the complex was examined by SDS- and native-PAGE ( Figure 6 B). We also noticed that HTT_HAP40 complex forms a multimer, which is contrast to the previous works ( Guo et al., 2018 ; Harding et al., 2021 ; Huang et al., 2021 ). However, it is possible that the multimer of HTT_HAP40 complex may be induced in high concentration, which is in our case.…”
Section: Expected Outcomescontrasting
confidence: 99%
See 2 more Smart Citations
“…The quality of the complex was examined by SDS- and native-PAGE ( Figure 6 B). We also noticed that HTT_HAP40 complex forms a multimer, which is contrast to the previous works ( Guo et al., 2018 ; Harding et al., 2021 ; Huang et al., 2021 ). However, it is possible that the multimer of HTT_HAP40 complex may be induced in high concentration, which is in our case.…”
Section: Expected Outcomescontrasting
confidence: 99%
“…Although the purified HTT protein can be pulled down with GST-HAP40, HTT_HAP40 does not form a stable complex when compared with the complex coexpressed, which is consistent with previous works ( Guo et al., 2018 ; Harding et al., 2021 ; Huang et al., 2021 ). These data demonstrated that the HTT complexes can be generated through this protocol.…”
Section: Expected Outcomessupporting
confidence: 92%
See 1 more Smart Citation